METHODOLOGY FOR EVALUATION OF STRATEGIC DOCUMENTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The nature of the strategic documents and the mechanisms for their updating require improvement of the strategic planning apparatus. Despite the existing actions in this direction, there is still no universal state standard and mature regulatory framework to harmonize and regulate the entire process in the Republic of Bulgaria. The report summarizes efforts to create a new toolkit bringing together proven practices in the subject area. A Methodology for the evaluation of strategic documents is presented, which offers a comprehensive and systematized approach to the evaluation of conformity according to the procedure of creation, structure, consistency, content and attainability.